Craniosynostosis: orofacial and oral health perspectives with masticatory insights - Yanisa Wongbanthit; Nond Rojvachiranonda; Soranun Chantarangsu; Preeya Suwanwitid; Wuttichart Kamolvisit; Thantrira Porntaveetus (BMC, 2024)
Abstract Background Craniosynostosis (CS), premature fusion of one or more cranial sutures, leads to abnormal skull development, impacting both facial esthetics and oral function. This study aimed to evaluate the specific orofacial and oral health characteristics, including masticatory performance, in Thai patients with CS. Methods A comparative study was conducted with Thai CS patients aged 6-17 years and a control group of healthy individuals with similar age distribution. Assessments included craniofacial morphology, oral health status, and masticatory performance. Intergroup comparisons utilized appropriate statistical tests. Results The study included 24 CS patients with a mean age of 10.11 ± 2.98 years and 30 controls. CS patients exhibited a significantly higher prevalence of various oral conditions compared to controls: cleft palate (20.8%), anterior open bite (41.7%), anterior crossbite (54.2%), posterior crossbite (50%), combined anterior-posterior crossbite (45.8%), dental crowding in both maxilla and mandible (50% and 45.8% respectively), congenitally missing teeth (50%), supernumerary teeth (12.5%), and eruption failure (54.2%). Furthermore, CS patients exhibited significantly higher caries prevalence and susceptibility, alongside poorer oral hygiene, compared to controls. Regarding jaw relationships, CS patients exhibited a significantly higher proportion of Angle's Class III malocclusion (50%) compared to the control group, where Class I malocclusion was predominant (50%). Masticatory performance, assessed using the two-color gum mixing ability test, showed significantly higher hue variance in CS patients (0.12 ± 0.07) compared to the control group, indicating reduced chewing performance. Conclusion This study underscores the significant orofacial and oral health challenges faced by children with CS, including a high prevalence of malocclusions, dental anomalies, elevated caries experience, and compromised masticatory function. These findings emphasize the importance of tailored interventions and comprehensive oral healthcare strategies to address the unique needs of this population and improve their overall quality of life.